Ontario post-secondary education funding policies: Perverse incentives and unintended consequences - Charles M. Beach; Frank Milne (Queen's University, Department of Economics, 2019)
This paper offers some observations on the funding of post-secondary schools in Ontario and Canada more broadly. Specifically, it notes how limited public funding for domestic students has provided strong incentives for PSE schools to attract full fee-paying international students, whose numbers have risen dramatically in recent years in Canada. The result has been a rising financial exposure of such schools to sudden external funding shocks and an increasing risk to the overall quality and available curriculum of programs delivered to all students. The paper also comments on Ontario plans for differentiation of schools, and raises concerns about Ontario's planned heavy reliance on performance-based funding rules. We explore unintended consequences of crude application of simplistic performance metrics using a number of examples from recent British and Australian experience.
Keywords: H52; I22; I23; 330; post-secondary education; international students; Ontario university funding incentives